Un enseignement en ligne presque invisible : une réponse à Christian Boyer et Steve Bissonnette - Allaire, Stéphane; Forest, Marie-Pier; Granger, Nancy; Tremblay, Mélanie; Monney, Nicole; Charland, Patrick; Giroux, Patrick (Revue internationale du CRIRES : innover dans la tradition de Vygotsky / CRI_SAS international Journal: Vygotsky's Heritage: Innovation in Education, 2022)
This paper offers an empirical critical look at studies cited as proof of the ineffectiveness of online teaching. Given the importance of considering the practices and activity of actors with a certain finesse when analyzing or evaluating any educational system, we have examined what information of this order is considered in a few large studies cited for their scientific rigour. We conducted a content analysis of the information provided on how the online teaching took place. The results bring important nuances to works that claim to report evidence concluding that online teaching is ineffective.
Keywords: digital education; données probantes; enseignement en ligne; evidence-based data; numérique; online teaching; pedagogical practices; pratiques pédagogiques; qualitative research; recherche qualitative